Manual on the management, maintenance and use of blood cold chain equipment : Safe blood and blood products. - Organization, World Health (World Health Organization, 2005)
The blood cold chain is a series of interconnected activities involving equipment, personnel and processes that are critical for the safe storage and transportation of blood from collection to transfusion. Breaks in the cold chain happen for many reasons, such as equipment that does not meet standards of quality and safety, is unsuitable for blood storage, or is not properly maintained or repaired. The major items of blood cold chain equipment are refrigerators, freezers and transport boxes. Temperature monitors are essential during storage and transportation, and alarms are fitted to storage.